ABORDAREA DEMERSULUI EDUCAŢIONAL ÎN CONTEXTUL ASPECTULUI LATERALIZĂRII CEREBRALE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2008)
A special interest for physiology represents the problem linked to the functional asymmetry of the brain. Those two hemispheres (left hemisphere and right hemisphere) of the human brain perceive and work out the information in different ways. It is known that a part of people have their left hemisphere predominating, whereas the others have the right one that predominates. For adequate and best involving of all the children in the process of learning, the lesson should include a lot of teaching activities/tasks and a corresponding teaching technology for balanced involving of brain hemispheres in the process of learning. This article includes examples of teaching methods and tasks, that contribute to the best involvement of every pupil in the educational process.